Orientation of the beta-hydroxyl group controls the diastereoselectivity during the hydride reduction and grignard reaction of inososes - Jagdhane, Rajendra C.; Patil, Madhuri T.; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Tetrahedron, 2013)
A comparison of the results of the Grignard reaction and the hydride reduction of the carbonyl group of epi- and scyllo-inososes reveals that the extent of diastereoselectivity of these reactions is decided by the orientation of the beta-hydroxyl group (or its derivative). Presence of an axial beta-hydroxyl group generally results in the formation of relatively larger amount of the axial alcohol as a result of the reduction of the carbonyl group. The possible reasons for the observed differences in diastereoselectivity between the reactions of these isomeric epi- and scyllo-inososes have been discussed. The sequence of reactions reported here provides convenient access to C-allcylated inositols, such as iso-laminitol and iso-mytilitol as well as 2-O-methyl epi-inositol, an epimer of the naturally occurring ononitol. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; diastereoselectivity; Grignard; Inositol; Nucleophile; reduction